1984
DOI: 10.1111/j.1533-8525.1984.tb00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mother and Father Influences on the Educational Attainment of Black and White Women

Abstract: This study examines the impacts of maternal and paternal influences on the educational attainment of women and whether these parental effects operate similarly for white and black women. Specifically, the study measures the differential effects of mother's and father's education, occupation, and encouragement. Using data from the National Longitudinal Survey of Labor Market Experience ( N U ) , 428 white and 145 black women were examined. Findings indicate different patterns in the way mothers and fathers affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, later studies were less consistent with the same-sex socialization model. Reeder and Conger (1984) concluded that among daughters, father's education was more important than mother's, but mother's occupation was more important than father's. Consistent with the same-sex socialization model, Crook (1995) found in that in Australia mothers' characteristics influenced their daughters' education more than their sons' but concluded that 'parents are no more likely to influence the educational and occupational attainment of their like-sexed than their opposite-sexed children'.…”
mentioning
confidence: 99%
“…However, later studies were less consistent with the same-sex socialization model. Reeder and Conger (1984) concluded that among daughters, father's education was more important than mother's, but mother's occupation was more important than father's. Consistent with the same-sex socialization model, Crook (1995) found in that in Australia mothers' characteristics influenced their daughters' education more than their sons' but concluded that 'parents are no more likely to influence the educational and occupational attainment of their like-sexed than their opposite-sexed children'.…”
mentioning
confidence: 99%
“…It appears that mothers' educational achievements and occupational positions are as crucial in predicting children's educational attainments. For many groups, including mothers' social background improves the prediction of educational attainment (Korupp, Ganzeboom and Van Der Lippe 2002, Reeder and Conger 1984, Rothon 2008. The present study shows that mothers' social and economic background is crucial and has to be included in the analysis in order to better understand educational attainment and help explaining the persistence of educational inequality in Israel.…”
Section: Insert Table 2 About Here 6 Discussion and Conclusionmentioning
confidence: 76%
“…This is likely because more Hispanic respondents did not know or did not report their mother’s education level relative to their father’s education. Thus, this study focuses on the effects of the difference in years of education between the respondent and their father, based on the historical educational context of this cohort and previous research suggesting educational level of fathers is more predictive of educational attainment (De Vries & De Graaf, 2008; Keage et al, 2016; Reeder & Conger, 1984), reason for attending college (Schlechter & Milevsky, 2010) and career aspirations (Khampirat, 2020). Race and years of education, along with other demographic information is maintained in the HRS Tracker File.…”
Section: Methodsmentioning
confidence: 99%